Smart Drug Delivery - Ahmad, Usama; Faheem Haider, Md; Akhtar, Juber (IntechOpen, 2022)
This book brings together recent developments in the field of drug delivery. Technological advancements in the field of pharmaceutical sciences have revolutionized the patient care industry. The book serves to bridge the gap between the current research scenario and the technical knowledge provided at the pharmaceutical institutions to maximize the skills of individuals involved at any level in this domain. Chapters address topics related to the formulation and evaluation of drug delivery systems, various targeting approaches and novel tools, and design and statistical techniques employed to develop robust and effective dosage forms.